Increasing strength of aircraft repaired parts / Mastuni Samiran and Mohd Fitri Mohd Yahya - Samiran, Mastuni; Mohd Yahya, Mohd Fitri (2000)
In this project entitle INCREASING STRENGTH OF AIRCRAFT REPAIRED PARTS, there are two sub-titles that are of major concern. The two sub-titles are: 1) Dimpling Process 2) Fiber Glass Repair. The Dimpling Process is a study that related with material like aluminum alloy and Fiber Glass Repair is a study that related with resin and fiber cloth. All the details about the project are reported. Further we hope that this report will assist the further students in getting practical information about strengthening aircraft parts. This report is written in two parts. The first part deals with strength of riveted joint and the second part deals with fiber glass repair.